2004
DOI: 10.1126/science.1103544
|View full text |Cite
|
Sign up to set email alerts
|

A Centrosomal Localization Signal in Cyclin E Required for Cdk2-Independent S Phase Entry

Abstract: Excess cyclin E-Cdk2 accelerates entry into S phase of the cell cycle and promotes polyploidy, which may contribute to genomic instability in cancer cells. We identified 20 amino acids in cyclin E as a centrosomal localization signal (CLS) essential for both centrosomal targeting and promoting DNA synthesis. Expressed wild-type, but not mutant, CLS peptides localized on the centrosome, prevented endogenous cyclin E and cyclin A from localizing to the centrosome, and inhibited DNA synthesis. Ectopic cyclin E lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
169
0
3

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 188 publications
(181 citation statements)
references
References 18 publications
8
169
0
3
Order By: Relevance
“…Although it has been described that cdk2 is not an essential gene in the mouse, (Berthet et al, 2003;Geng et al, 2003;Ortega et al, 2003;Tetsu and McCormick, 2003) an overexpression of cdk2 with associated cyclins has been shown in several tumors (Al-Aynati et al, 2004;Olofsson et al, 2004). Furthermore, cdk2 has been recently found to be required for centrosome duplication in mammalian cells (Matsumoto et al, 1999;Matsumoto and Maller, 2004) suggesting that inhibition of cdk2 activity would be an effective anticancer approach. In addition, cdk2 has rapidly emerged as a potential inhibition target by small molecule drugs that will hopefully lead to the development of effective therapies for proliferative disorders (Gibbs and Oliff, 1994;Senderowicz, 2003 We were therefore led to generate a molecular tool that provides a mechanism-based model for the inhibition of cdk2 activity.…”
Section: Discussionmentioning
confidence: 99%
“…Although it has been described that cdk2 is not an essential gene in the mouse, (Berthet et al, 2003;Geng et al, 2003;Ortega et al, 2003;Tetsu and McCormick, 2003) an overexpression of cdk2 with associated cyclins has been shown in several tumors (Al-Aynati et al, 2004;Olofsson et al, 2004). Furthermore, cdk2 has been recently found to be required for centrosome duplication in mammalian cells (Matsumoto et al, 1999;Matsumoto and Maller, 2004) suggesting that inhibition of cdk2 activity would be an effective anticancer approach. In addition, cdk2 has rapidly emerged as a potential inhibition target by small molecule drugs that will hopefully lead to the development of effective therapies for proliferative disorders (Gibbs and Oliff, 1994;Senderowicz, 2003 We were therefore led to generate a molecular tool that provides a mechanism-based model for the inhibition of cdk2 activity.…”
Section: Discussionmentioning
confidence: 99%
“…This CLS has similar properties as other centrosome-targeting domains from proteins like AKAP450, Cyclin A, Cyclin E, which displace their endogenous proteins from centrosomes when overexpressed. [27][28][29][30] These CLS domains interact with scaffold proteins important for centrosome localization and functions of their endogenous proteins.…”
Section: Discussionmentioning
confidence: 99%
“…45 However, the localization of cyclin E1 to the centrosome is controlled by the CLS encoded in exon 9, which has a critical effect on S phase entry and DNA synthesis independently of cdk2. 37 As in the ⌬3/8 isoform lacking the NLS but still containing an intact CLS, we speculated that ⌬3/8 should be restrained to the cytoplasm. In fact, our experiments clearly demonstrated that ⌬3/8 was exclusively located in the cytoplasm and failed to undergo nuclear import in parallel with cdk2 in quiescent cells.…”
Section: Discussionmentioning
confidence: 99%